2021
DOI: 10.1002/adma.202101536
|View full text |Cite
|
Sign up to set email alerts
|

Strong Metal–Support Interaction for 2D Materials: Application in Noble Metal/TiB2 Heterointerfaces and their Enhanced Catalytic Performance for Formic Acid Dehydrogenation

Abstract: Strong metal–support interaction (SMSI) is a phenomenon commonly observed on heterogeneous catalysts. Here, direct evidence of SMSI between noble metal and 2D TiB2 supports is reported. The temperature‐induced TiB2 overlayers encapsulate the metal nanoparticles, resulting in core–shell nanostructures that are sintering‐resistant with metal loadings as high as 12.0 wt%. The TiOx‐terminated TiB2 surfaces are the active sites catalyzing the dehydrogenation of formic acid at room temperature. In contrast to the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 74 publications
(36 reference statements)
3
42
0
Order By: Relevance
“…The binding energy at 188.1 eV belongs to the B in TiB 2 , and the binding energy at 192.1 eV is attributed to metaborate (BO x ) species. 30,31 32,33 XPS analysis confirms that we successfully loaded TiB 2 on the surface of α-Fe 2 O 3 ; the surface oxidized layer is composed of BO x by subsequent calcination process, in accordance with the result of HRTEM.…”
Section: Morphology and Structuresupporting
confidence: 75%
See 1 more Smart Citation
“…The binding energy at 188.1 eV belongs to the B in TiB 2 , and the binding energy at 192.1 eV is attributed to metaborate (BO x ) species. 30,31 32,33 XPS analysis confirms that we successfully loaded TiB 2 on the surface of α-Fe 2 O 3 ; the surface oxidized layer is composed of BO x by subsequent calcination process, in accordance with the result of HRTEM.…”
Section: Morphology and Structuresupporting
confidence: 75%
“…There are two peaks for α-Fe 2 O 3 , containing lattice oxygen (529.8 eV) and hydroxyl groups (531.3 eV). But the O 1s spectra of α-Fe 2 O 3 /SO-TiB 2 could be divided into lattice oxygen (530.1 eV), B-O bond (532.3 eV) and hydroxyl groups (531.5 eV) 32,33. XPS analysis confirms that we successfully loaded TiB 2 on the surface of α-Fe 2 O 3 ; the surface oxidized layer is composed of BO x by subsequent calcination process, in accordance with the result of HRTEM.…”
mentioning
confidence: 99%
“…We found that interfacial properties like the adhesion energies on two-, three-, and four-layered TiO 2 supports are almost identical (see the Supporting Information). A dipole correction along the z -direction is used to avoid spurious electrostatic interactions between periodic slabs separated by a vacuum. , We employed numerical cutoffs for total energies and forces of 10 –7 eV and 0.05 eV Å –1 , respectively. We applied a Fermi Dirac smearing of 0.1 eV to the electronic states to facilitate numerical convergence of the self-consistent loop.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Li et al have optimized MSI on Pt loaded on layered TiB 2 (Pt/TiB2, 16) to yield hydrogen productivity of 13.8 mmol g cat −1 h −1 in 10 M FA solution under additive-free conditions. [80] On the other hand, Pd catalysts supported nanoporous carbon (Pd/C; 17) have shown the TOF of 9110 h −1 at 60 °C using an equimolar FA-SF (sodium formate) solution. [81] Monometallic nanoparticles with strong CO adsorption strengths are prone to deactivation in the aqueous phase FA dehydrogenation due to poisoning.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%